ADAPTATION OF VALUES AND ARCHITECTURAL FORMS OF JAVANESE HOUSE IN THE TOURISM AREA OF BEJIHARJO VILLAGE AS PART OF CULTURAL TOURISM VILLAGE PLANNING IN THE SPECIAL REGION OF YOGYAKARTA - Bachtiar Fauzy; Indri Astrina Wirakusumah; Caecilia Srikanti Wijayaputri; Handoko Sutanto; Rochana Esti Pramesti; Alvin Fernandez Komar; Christella Sharleen; Ghiffari Mohammad Alfarisyi (Ide dan Dialog Desain Indonesia (Idealog), 2021)
The existence of villages which rich in cultural and natural potential is still being managed poorly, both in physical and non-physical aspects, specifically in the attempt to support the village development which still requires comprehensive supervision. This study is considered important for an intensive in-depth study. Referring to the potential possessed by Bejiharjo Village, this study includes physical and non-physical aspects that can be utilize in developing the existing elements in the scope of the built environment in the Bejiharjo Village area based on the lacalities values. The purpose of this study is to evaluate the existing condition of Bejiharjo Village to provide design recommendations for the development of Bejiharjo village into an tourism village. The method of documentation carried out is divided into 3 (three) stages. The first stage is documentation of literature that is reviewed and used as the basis for exploring the potential and problems in Bejiharjo Village. The second stage is surveys and interviews, both with village officials and with the community, this stage is carried out several times to obtain more accurate data. The third stage is to review and sort out the results of surveys and interviews, as a basis for designing a tourist village area. The benefits of this study are expected to provide recommendations in the form of a design for a culturally based tourism village area. This study can also be used as a basis or guide in preparing architectural documentation methods to support the masterplan as one of the strategies in developing the Bejiharjo Village area into a cultural based tourism village. Keywords : Architectural Planning, Javanese House Architecture, Bejiharjo Village area, Cultural Tourism, Special Region of Yogyakarta